Hubungan Minat Baca dengan Hasil Belajar IPS di Sekolah Dasar - sari, kurnia mayang; Zuraida, Zuraida; Taufik, Taufina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research aims to know whether or not the significant relationship between reading interest and learning result in learning subject of social knowledge in fifth grade at SD Negeri se-Gugus I, Sungai Pua District, Agam Regency. The method of this research is correlation. . Sampling data is taken by cluster random sampling technique. The sample of this study amounted to 55 people with a population of 220 people. Based on the data analysis that had been collected, it is known that there is a positive significant relationship between reading interest and learning result of social subject in fifth grade SDN Se-Gugus Sungai Pua District, Agam Regency. This is proved by counted-r is 0.724 > 0.2656 , and the significant value is 0.000,<0.05. It means that every enhancement of reading interest is followed by the enhancement of learning result in learning social knowledge, and vice versa Keywords: learning interest, learning outcomes,  IPS